درجة أهمية تنويع مصادر تمويل تعليم الفتاة الريفية في الجمهورية اليمنية - منتهى, الشكري (جامعة الوادي - University of Eloued, 2023)
هدف البحث إلى التعرف على درجة أهمية تنويع مصادر تمويل تعليم الفتاة الريفية في الجمهورية اليمنية، واستخدمت الباحثة المنهج الوصفي المسحي، والاستبانة أداة لجمع البيانات والمعلومات، وتكون مجتمع البحث من مجموعة من الخبراء المتخصصين في الإدارة والتخطيط التربوي ومن القيادات في مكاتب التربية والتعليم في الجمهورية اليمنية، وتم اختيار عينة قصدية منهم بلغت (26) خبيرًا ومن المشاركين في جولات دلفي المعدل، وتوصل البحث إلى عدد من النتائج أهمها: ارتفاع المتوسط الإجمالي العام لمستوى موافقة الخبراء المشاركين نحو درجة أهمية تنويع مصادر تمويل تعليم الفتاة الريفية في الجمهورية اليمنية؛ إذ جاءت بدرجة (مرتفعة)، وبمتوسط حسابي إجمالي (3.39)، وبانحراف معياري إجمالي (0.50)، ونسبة موافقة بلغت (85%)، وتوصل البحث إلى عدد من التوصيات والمقترحات ذات العلاقة بموضوع البحث. Abstract : The aim of the current research is to identify the degree of importance of diversifying the sources of financing the education of rural girls in the Republic of Yemen, and the researcher used the descriptive survey method, and the questionnaire as a tool for collecting data and information. The research community consisted of a group of experts specialized in management and educational planning and leaders in the Office of Education in the Republic of Yemen, and an intentional sample of them was selected, amounting to (26) experts and participants in the average Delphi tours. The research reached a number of results, the most important of which is that the overall average The level of approval of the participating experts towards the degree of importance of diversifying the sources of funding for rural girls’ education in the Republic of Yemen came at a (high) degree, with a total mean of (3.39), with a total standard deviation of (0.50), and an approval rate of (%85). Relationship to the research topic.
مقال
Keywords: (Education funding – Education rural girl